Pregnancy Outcomes in Patients With Multiple Sclerosis Exposed to Natalizumab—A Retrospective Analysis From the Austrian Multiple Sclerosis Treatment Registry - Guger, Michael; Traxler, Gerhard; Drabauer, Martina; Leitner-Pohn, Doris; Enzinger, Christian; Leutmezer, Fritz; Oel, Dierk; Di Pauli, Franziska; Berger, Thomas; Ransmayr, Gerhard (Frontiers in Neurology, 2020)
Objectives: To analyze safety and impact of natalizumab (NTZ) exposure on disease course, pregnancy and newborn outcomes of relapsing-remitting multiple sclerosis (RRMS) patients from the Austrian Multiple Sclerosis Treatment Registry (AMSTR). Materials and methods: Twelve pregnancies of eleven women with RRMS exposed to treatment with NTZ were identified from the AMSTR. Exposure to NTZ was defined as treatment with NTZ from eight weeks prior to the start of the last menstrual period and onward. All patients completed a standardized questionnaire regarding pregnancy and newborn outcomes until the postpartum period for up to twelve months. Results: NTZ was stopped on average 46 days after last menstrual period. There were eleven live births and one elective termination due to ectopic pregnancy. Mean gestational age of live born individuals was 39.0 weeks (standard deviation [SD] ± 1.1). Mean birth weight and length were 3426 g (SD ± 348) and 51.9 cm (SD ± 1.9), respectively. APGAR-Scores one minute after birth were normal with 9.2 points on average. One child displayed hip dysplasia as the only congenital malformation documented in this cohort. Three patients experienced relapses during pregnancy and three patients in the postpartum period, resulting in confirmed Expanded Disability Status Scale (EDSS) progression in four of them. Conclusion: In this cohort there was no increased risk concerning pregnancy and newborn outcomes due to NTZ exposure. However, relapses occurring during pregnancy and postpartum period resulted in confirmed disability.